Internalisasi Nilai-nilai Karakter melalui Pengelolaan Kelas pada Pembelajaran SKI di Madrasah Tsanawiyah: Internalization of Character Values through Classroom Management in the Teaching of Islamic Cultural History (SKI) at Madrasah Tsanawiyah - Mulyawati, Susi Sri; Nugraha, Mulyawan Safwandy; Aliyah, Adah; Yani, Ahmad (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
This study investigates the process of internalizing character values through Islamic Cultural History (SKI) learning in Madrasah Tsanawiyah, focusing on effective classroom management strategies. Using a qualitative case study method, the research involved observations, interviews with teachers, and analysis of student reflections. The findings reveal a three-phase internalization model: (1) establishing a conducive learning environment through religious opening rituals, (2) integrating character values into subject matter via group discussions and case studies, and (3) reinforcing values through reflective practices. Results demonstrate significant improvements in students' positive attitudes (85% participation rate) and disciplinary behavior (70% compliance increase), particularly through verbal reinforcement and symbolic rewards. However, challenges persist in maintaining behavioral consistency outside classroom settings and limited parental involvement. The study highlights the crucial role of structured classroom management in character education while emphasizing the need for multimedia learning tools and extended learning time. These outcomes contribute to theoretical frameworks of value internalization and offer practical insights for Islamic education practitioners seeking to balance academic and character development objectives in madrasah curricula.